Spectrum Sensing for Cognitive Coexistent Heterogeneous Networks. (1st October 2013) - Zhao, Bingxuan; Sasaki, Shigenobu
Abstract : This paper proposes a noncoherent spectrum sensing scheme for the cognitive coexistent heterogeneous networks with the assistance of geolocation information of primary and secondary nodes. Different from the conventional networks with single secondary network, the spectrum sensing scheme in the coexistence scenario should not only detect the primary signal but also detect the secondary signals to avoid the interference with both the primary network and the operating coexistent secondary networks. Therefore, the sensing scheme in this case should be able to differentiate the primary signal from each kind of the secondary signals. However, in the coexistent heterogeneous scenarios, the secondary signals may exploit different PHY modes (some of them may be the same as the primary PHY mode), which imposes difficulties in the coherent signal detection schemes. Aiming to tackle this problem, the parallel detection of both primary signal and each kind of secondary signals is implemented through a proposed noncoherent power decomposition scheme. In this scheme, the power decomposition is formulated into a problem of solving a nonhomogeneous linear equation matrix. During the signal detection, the characteristics of both primary and secondary signals are not required. Both the analysis and the simulation results show the feasibility and efficiency of the proposed scheme.